I+: A multiparadigm language for object-oriented declarative programming - Ng, K.W.; Luk, C.K. (Computer languages, 1995)
This paper presents a multiparadigm language I + which is an integration of the three major programming paradigms: object-oriented, logic and functional. I + has an object-oriented framework in which the notions of classes, objects, methods, inheritance and message passing are supported. Methods may be specified as clauses or functions, thus the two declarative paradigms are incorporated at the method level of the object-oriented paradigm. In addition, two levels of parallelism may be exploited in I + programming. Therefore I + is a multiparadigm language for object-oriented declarative programming as well as parallel programming.